Informing children citizens efficiently to better engage them in the fight against COVID-19 pandemic. - Jean-Eric Ghia; Sophie Gaulin; Laure Ghia; Laure Garancher; Claude Flamand (Public Library of Science (PLoS), 2020)
Since the beginning of the year, the world's attention has rightly been focused on the spread of the Coronavirus Disease 2019 (COVID-19) pandemic and the implementation of drastic mitigation strategies to limit disease transmission. However, public health information campaigns tailored to children are very rare. Now more than ever, at a time when some governments are taking populations out of lockdown and youth are returning to schools, children around the world need to fully grasp the modes of transmission of the disease, the health risks, the scientific notions of the immune system, the value of barrier measures, and the progress of scientific research. In the context of the COVID-19 pandemic, comics can be very useful for communicating quickly and effectively abstract and important information to children who might be under the influence of a large amount of sometimes contradictory information. Conveying precise, reliable, and accessible information to children is key in a world overwhelmingly impacted by the outbreak. This should be the role and the responsibility of world health official leaders and governments in compliance with the United Nations Convention on the Rights of the Child. In partnership with mainstream medias, consortia of scientists, communication experts, and education specialists, it is urgent that world leaders engage children in this worldwide public health fight.